Bioengineering models of female reproduction - Zubizarreta, Maria E.; Xiao, Shuo (Bio-design and manufacturing, 2020)
The female reproductive system consists of the ovaries, the female gonads, and the reproductive tract organs of the fallopian tubes, uterus, cervix, and vagina. It functions to provide hormonal support and anatomical structure for the production of new offspring. A number of endogenous and exogenous factors can impact female reproductive health and fertility, including genetic vulnerability, medications, environmental exposures, age, nutrition, and diseases. To date, due to the ethical concerns of using human subjects in biomedical research, the majority of studies use in vivo animal models and 2D cell/tissue culture models to study female reproduction. However, the complexity and species difference of the female reproductive system in humans make it difficult to compare to those of animals. Moreover, the monolayered cells cultured on flat plastics or glass lose their 3D architecture as well as the physical and/or biochemical contacts with other cells in vivo. Further, all reproductive organs do not work alone but interconnect with each other and also with non-reproductive organs to support female reproductive, endocrine, and systemic health. These facts suggest that there is an urgent and unmet need to develop representative, effective, and efficient in vitro models for studying human female reproduction. The prodigious advancements of bioengineering (e.g., biomaterials, 3D printing, and organ-on-a-chip) allow us to study female reproduction in an entirely new way. Here, we review recent advances that use bioengineering methods to study female reproduction, including the bioengineering models of the ovary, fallopian tube, uterus, embryo implantation, placenta, and reproductive disease.